Karyotypic conservatism in samples of Characidium cf. zebra (Teleostei, Characiformes, Crenuchidae): physical mapping of ribosomal genes and natural triploidy - Pansonato-Alves, José Carlos [UNESP]; Oliveira, Claudio [UNESP]; Foresti, Fausto [UNESP] (Sociedade Brasileira de Genética, 2011)
Basic and molecular cytogenetic analyses were performed in specimens of Characidium cf. zebra from five collection sites located throughout the Tietê, Paranapanema and Paraguay river basins. The diploid number in specimens from all samples was 2n = 50 with a karyotype composed of 32 metacentric and 18 submetacentric chromosomes in both males and females. Constitutive heterochromatin was present at the centromeric regions of all chromosomes and pair 23, had additional interstitial heterochromatic blocks on its long arms. The nucleolar organizer regions (NORs) were located on the long arms of pair 23, while the 5S rDNA sites were detected in different chromosomes among the studied samples. One specimen from the Alambari river was a natural triploid and had two extra chromosomes, resulting in 2n = 77. The remarkable karyotypic similarity among the specimens of C. cf. zebra suggests a close evolutionary relationship. on the other hand, the distinct patterns of 5S rDNA distribution may be the result of gene flow constraints during their evolutionary history.
Keywords: Characidium; heterochromatin; 18S rDNA; 5S rDNA; natural triploidy